Alcohol consumption and tobacco exposure among pregnant women in Ibadan, Nigeria - Ikeola A. Adeoye (BMC Psychiatry, 2022)
Abstract Background Alcohol consumption and tobacco exposure during pregnancy are hazardous behaviours which are increasing significantly in low and middle-income countries, including sub-Saharan Africa. However, they have received little attention in Nigeria’s maternal health research and services. The prevalence, pattern and predictors of alcohol consumption and tobacco exposure among pregnant women in Ibadan, Nigeria, were investigated. Methods This is a part of a prospective cohort study among pregnant women in Ibadan, Nigeria (Ibadan Pregnancy Cohort Study (IbPCS), which investigated the associations between maternal obesity, lifestyle characteristics and perinatal outcomes in Ibadan. Alcohol consumption and tobacco exposure of 1745 pregnant women were assessed during enrollment by self-reports using an interviewer-administered questionnaire. Bivariate and multiple logistic regression analyses examined the associations at a 5% level of statistical significance. Results The prevalence of pre-pregnancy alcohol consumption and alcohol consumption during pregnancy were 551 (31.7%) and 222 (12.7%), respectively, i.e. (one in every eight pregnancies is exposed to alcohol). Palm wine (52%) and beer (12%) were the most common alcohol consumed among pregnant women. The predictors of alcohol consumption during were pre-pregnancy alcohol use [AOR = 10.72, 95% CI: 6.88–16.70) and religion i.e. Muslims were less likely to consume alcohol during pregnancy compared to Christians: [AOR = 0.60, 95% CI: 0.40–0.92). The prevalence of tobacco exposure in the index pregnancy was 64 (3.7%), i.e. one in every 27 pregnancies is exposed to tobacco. In contrast, cigarette smoking, second-hand smoke and smokeless tobacco were 0.4, 1.7 and 1.8%, respectively. Pre-pregnancy cigarette smoking was reported by 33(1.9%) and was the most significant predictor [AOR = 12.95; 95% CI: 4.93, 34.03) of tobacco exposure during pregnancy in our study population. Conclusions Alcohol consumption and tobacco exposure are not uncommon and have been an ongoing but neglected threat to maternal and child health in Nigeria. Alcohol and tobacco control policy and programmes to prevent the use among pregnant and reproductive-age women in Nigeria should be implemented primarily during antenatal care.